Hubungan antara Kompetensi Guru dengan Hasil Belajar Siswa pada Mata Pelajaran Sejarah Di SMA Negeri Kota Bandung - Baiti Nur Atika; Yani Kusmarni (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2017)
This thesis entitled The Relationship Between Teacher Competence with Learning Outcomes On History Lesson In Bandung Senior High School. Background research on this variable appears as a form of interest the authors of the implementation of the Teacher Competency Test (UKG) 2015 years ago. The main issues discussed in this essay is 'Is there a connection between the competence of teachers to student learning outcomes in the subjects of history in Bandung Senior High School?'. The method used in this thesis is descriptive analysis method through correlational studies is to study the relationship between two variables, the competency of teachers (X) with the learning outcomes (Y). Data were obtained from questionnaires and documentation study. Subjects in this study is a history teacher and student of Senior High School in Bandung into the sample. Then the data is processed by using the Pearson product moment formula. The results showed that from the processing of these data it is concluded that the value of the correlation coefficient (r xy) of -0.377 * while r table at 0,361 at N = 30, with a significance level of 5%. This means that the value is greater than r rxy table (0.377 * 0.361). Then H0 rejected and Ha accepted which states that there is a relationship between the competence of teachers to student learning outcomes in the subjects of history in Bandung Senior High School. Only the results of which showed negative values are marked with a dash (-). That is the direction do the opposite direction, or it can be said better history teacher competence, the lower the students' learning outcomes.